The effect of deep breath relaxation and counterpressure massage on pain reduction during labor - Rahmawati Wahyuni; Supriadi Supriadi; Dewi Susanti; Nursari Abdul Syukur; Rosalin Ariefah Putri (PAGEPress Publications, 2024)
Labor pain is a manifestation of the contraction (shortening) of the uterine muscles. Non-pharmacological treatment in pain management, namely deep breathing relaxation and counterpressure massage is an alternative method and a new trend that can be developed. This study investigated the effectiveness of deep breathing relaxation and Counterpressure massage in alleviating labor pain during active phase I. Employing a quasi-experimental design with a two-group pre-test post-test approach, 30 postpartum mothers from June to July 2021 were consecutively sampled. Deep breathing relaxation (5 times for 3-5 minutes) and counterpressure massage (3 times for 30-90 seconds) served as the independent variables, while pain intensity during the first active phase was the dependent variable. Utilizing the Wilcoxon and Mann Whitney tests at a 5% significance level, significant reductions in pain intensity were observed after both interventions (p-values: 0.002 for deep breathing, 0.046 for counterpressure massage). These non-pharmacological methods, enhancing endorphin release, contribute to relaxation and pain intensity reduction during labor. The findings underscore the potential of integrating deep breathing relaxation and counterpressure massage as effective approaches in non-pharmacological labor pain management.